PENGGUNAAN MEDIA SOSIAL OLEH WARTAWAN JAWA POS RADAR SEMARANG DALAM PEMBUATAN BERITA - Ova Adelia; S. Rouli Manalu (Interaksi Online, 2019)
This study aims to find out how social media use by Jawa Pos Radar Semarang’s journalist in making news. In addition, it is also to find out the reasons for using social media, what social media is used, and the contribution made by the use of social media to Jawa Pos Radar Semarang’s journalist (positive or negative). This is motivated by the widespread use of social media in traditional media practices which creates a gap because of the polarization of the impact felt by traditional media journalists. In this study using a intrinsic case study approach using explanatory analysis methods. The subjects of this study consisted of six the informant was the Jawa Pos Radar Semarang’s journalist who used social media with several methods of data collection, including documentation, archival recordings, open-ended interviews, field observations, and participant observation. The results of this study found the conclusion that the use of social media by Jawa Pos Radar Semarang journalists in making news was indeed proven in several stages, namely the stages of news planning, news editing, and news publishing. The researcher concluded that from the use of social media, Jawa Pos journalist Radar Semarang received a positive contribution because social media provided benefits in terms of data transfer, speed of information, and ease of sharing, considering that in carrying out their work practices, journalists were still guided by the Press Law and Code of Ethics Journalism.